ANALISA PENGENDALIAN KUALITAS PADA PROSES BAGGING PRODUK POLIPROPILENA DENGAN PENDEKATAN METODE SIX SIGMA DI PT. CHANDRA ASRI PETROCHEMICAL TBK - Hambali, Ikbal; Rahmatullah, Asep; Huda, Miftahul (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
PT. Chandra Asri Petrochemical Tbk. is a petrochemical company that experienced bag defects in the process of bagging polypropylene products exceeding the tolerance limit. The company sets a maximum bag defect limit of 0.028% of bagging production capacity. This study aims to control quality by calculating the sigma value of defect types and providing suggestions for improvement based on the factors causing defects. The method used is Six Sigma with DMAIC (Define, Measure, Analyze, Improve, Control). The analyzed data is bagging and bag defect production data for the period April 2023 to March 2024. The results showed that the percentage of bag defects was reduced from 0.051% to 0.034% after improvement. After improvement were carried out there was no data that was outside the control limits, and also the sigma value increased from 5.08 to 5.19. The main causes of bag defects are poor bagging machine maintenance, operators who are less focused and thorough, and implementing different SOPs. The company's proposed improvements include improving bagging machine maintenance, creating an SOP that requires checking seal results periodically, and updating the SOP